2009
DOI: 10.1093/bioinformatics/btp539
|View full text |Cite
|
Sign up to set email alerts
|

CCHMM_PROF: a HMM-based coiled-coil predictor with evolutionary information

Abstract: piero@biocomp.unibo.it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 33 publications
1
40
0
Order By: Relevance
“…This study found the CCHMM_PROF algorithm to give the best indicator of coiled-coil; however, it does not yield a registry prediction for the coiled-coil. Thus, it was not used in this study (61). Multicoil2 also performed well, but its results were consistent with that of MARCOIL and COILS-28 (62).…”
Section: Coiled-coil Predictions Do Not Accurately Reflect the Startsupporting
confidence: 58%
“…This study found the CCHMM_PROF algorithm to give the best indicator of coiled-coil; however, it does not yield a registry prediction for the coiled-coil. Thus, it was not used in this study (61). Multicoil2 also performed well, but its results were consistent with that of MARCOIL and COILS-28 (62).…”
Section: Coiled-coil Predictions Do Not Accurately Reflect the Startsupporting
confidence: 58%
“…Secondary structure was predicted using PSIPRED 18 , whereas domains, repeats and other features were predicted with InterproScan 19 . COILS 20 , MARCOIL 21 and CCHMM-PROF 22 were used to assess previously predicted coiled-coil regions, and TPR modules were predicted with TPRpred 23 . A repeat consensus was manually curated with Jalview from the MAFFT alignment.…”
Section: Methodsmentioning
confidence: 99%
“…The amino acid sequences of kRz and the unrelated functional equivalent from T7, gp18.5, were examined for their propensity to form coiled-coils through the use of the COILS 29 and CCHMM_PROF 30 programs.…”
Section: Coiled-coil Predictionmentioning
confidence: 99%